2018
DOI: 10.1038/s41598-018-33224-1
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Serum Free Fatty Acids are Indicators for Progression of Pre-leukaemia Diseases to Leukaemia

Abstract: Acute Leukaemia (AL) is a neoplasm of WBCs (white blood cells). Being an important class of metabolites, alteration in free fatty acids (FFAs) levels play a key role in cancer development and progression. As they involve in cell signaling, maintain membrane integrity, regulate homeostasis and effect cell and tissue functions. Considering this fact, a comprehensive analysis of FFAs was conducted to monitor their alteration in AL, pre-leukaemic diseases and healthy control. Fifteen FFAs were analyzed in 179 seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Lipid metabolism is a wide and intertwined network that mediates multiple functions, such as energy production [1], thermoregulation [2] and the synthesis of signaling molecules [3], while studies have demonstrated that abnormal levels of lipids contribute to numerous pathologies such as cardiovascular diseases, metabolic diseases and cancer [4]. Fatty acid imbalances have a prognostic value, as their levels in serum can act as tumor biomarkers, or they can predict responses to therapy in multiple cancer types, including leukemia [5], non-small cell lung cancer [6,7], breast cancer [8] and colorectal cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid metabolism is a wide and intertwined network that mediates multiple functions, such as energy production [1], thermoregulation [2] and the synthesis of signaling molecules [3], while studies have demonstrated that abnormal levels of lipids contribute to numerous pathologies such as cardiovascular diseases, metabolic diseases and cancer [4]. Fatty acid imbalances have a prognostic value, as their levels in serum can act as tumor biomarkers, or they can predict responses to therapy in multiple cancer types, including leukemia [5], non-small cell lung cancer [6,7], breast cancer [8] and colorectal cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, as the only FA significantly different between the stages, C14:0 was overexpressed in stage III-IV compared to stage 0-I, suggesting an association with melanoma progression. High serum levels of free C14:0 were also identified as an indicator for systematic progression of pre-leukemic conditions towards acute myeloid leukemia [77]. Moreover, C14:0 increase was related to risk of breast cancer occurrence in a nested case-control study [78].…”
Section: Discussionmentioning
confidence: 99%
“…Membrane biomass is generated by phospholipid biosynthesis that uses fatty acids as building blocks, with FA pools replenished by some combination of triglyceride catabolism, transporter-mediated uptake, and de novo synthesis via the ACLY/ACACA/FASN palmitate production pathway using citrate precursor diverted from the TCA cycle. Indeed, the role of lipid metabolism in AML progression is indicated by changes in serum lipid content 62 , in particular for long-chain saturated fatty acids that are the terminal product of the FAS pipeline. Inhibition of FA synthesis is therefore an appealing chemotherapeutic intervention 63,64 and FASN inhibitors are currently undergoing clinical trials for treatment of solid tumors and metabolic diseases 40 .…”
Section: Variation In Fatty Acid Metabolism In Aml Cellsmentioning
confidence: 99%